Critical issue in communication looking inward for answers(essays in honour of K.E.Eapan) - Eapan, K E; Melkate, Srinivas R; Rao, Sandhya (New Delhi Sage, 2000)
Critical issues in communication comprises original essays of currently challenged media, communication and the media. The scope of the discussions ranges from the political economy of communication and information, and media in development ,to communicat
Keywords: Communication; Communication-India